Women's reflections on fertility and motherhood after breast cancer and its treatment. (14th January 2014) - Kirkman, M.; Winship, I.; Stern, C.; Neil, S.; Mann, G.B.; Fisher, J.R.W.
<x xml:space="preserve">Abstract</x> Breast cancer and its treatment have complex ramifications for women of reproductive age, including reduced fertility. With the aim of increasing understanding of what it means to women to manage fertility and motherhood in the years after a diagnosis of breast cancer, in‐depth qualitative interviews were conducted with 10 women aged 26–45 years, living in Victoria, Australia, who had been diagnosed with breast cancer aged 25–41. Transcripts were analysed thematically and interpreted within narrative theory. Six themes linking breast cancer to fertility and motherhood were identified: diagnosis as a pivotal life event, robbed of time and choice, significance of fertility, being a mother, narrative justification, and life after breast cancer treatment. Women without children described a preoccupying sorrow about lost fertility. Women's accounts yielded evidence of narrative meaning‐making, including justifying their decisions and actions in relation to survival, treatment and fertility, and coping with adversity by developing consoling plots. Breast cancer, fertility and reproductive health are inter‐linked in diverse ways which have immediate and long‐term consequences. Even if women are receiving optimum fertility management, it is evident that some women of reproductive age will need continuing post‐cancer care to manage and ameliorate ramifications of diminished or lost fertility.